Ewagriusz z Pontu, Pisma ascetyczne, t. 1, tłum. K. Bielawski, M. Grzelak, E. Kędziorek, o. L. Nieścior, A. Ziernicki, „Źródła Monastyczne" 18, Tyniec-Kraków 1998, Wydawnictwo Benedyktynów, ss. 432 - Woźniak, Paweł (Vox Patrum, 1998)
review